Comparisons of Sustainability Behaviors Pre- and Early Pandemic Among Botanical Garden Members - Mascatelli, Katilyn; Drummond Otten, Caitlin; Piacentini, Richard V.; Wong-Parodi, Gabrielle; States, Sarah L. (Frontiers in Sustainable Cities, 2021)
The COVID-19 outbreak drastically altered the behaviors of millions of Americans in 2020, including behaviors that contribute to carbon emissions. As many Americans stayed home midyear, environmental groups noted the decrease in driving and transportation-related pollution, theorizing that the pandemic could have a positive impact on the environment by decreasing individuals’ carbon emissions. However, it is dubious that individuals will behave in a more eco-friendly manner under the uncertain and stressful conditions of a global pandemic simply because they are more likely to be confined to their homes. We examined sustainability behaviors in 2018 and in the early pandemic in 2020 among a sample of members of a U.S., botanical garden. We surveyed members in May-July 2018, asking whether they had or had not done 11 sustainability behaviors (e.g., used alternative transportation, took shorter showers) in the past month. We resurveyed members about their engagement in those behaviors in April 2020 as well as to recall their engagement in those behaviors pre-pandemic in February 2020. We examined differences in self-reported behaviors among respondents who had taken both the May-July 2018 and April 2020 surveys (matched group n = 227), and then among respondents who had taken either the May-July (n = 1057) or the April 2020 survey (n = 881), but not both. Respondents in the matched group were more likely to report recycling, reducing red meat consumption, eating a plant-based diet, and reducing food waste in April 2020 compared to May-July 2018; they were less likely to compost, check the air in their tires, and use a smart thermostat. However, these differences also emerged when examining recalled behavior in February 2020, suggesting that matched group respondents’ self-reports may reflect changes in behavior over time rather than due to the pandemic. The unmatched group was more likely to reduce food waste but less likely to use alternative transportation to commute, check the air in their tires for fuel efficiency, and recycle in April 2020 compared to May-July 2018. Thus, few changes in sustainability behaviors can be attributed to the pandemic, but those that do involve personal travel or home confinement.